Determinants of vitamin D deficiency among Bangladeshi children: A hospital based case-control study - Mohammad Delwer Hossain Hawlader; Sanjana Zaman; Moshiur Rahman; Mohammad NM Khan; Aazia Hossain; Gias U Ahsan (Epidemiology, Biostatistics and Public Health)
Background: Risk factors of vitamin D deficiency among children have been identified in many developed countries but not yet in some developing countries like Bangladesh. Therefore, the aim of this study was to identify the determinants of vitamin D deficiency among Bangladeshi children. Methods: This case-control study was conducted at 2 paediatric hospitals in Dhaka city from January to June 2017. We recruited 198 vitamin D deficient cases and 198 apparently healthy controls. Data were analyzed using IBM SPSS, where quantitative variables were analyzed using descriptive statistics. The association between vitamin D deficiency with different lifestyle and dietary factors were analyzed by using Chi-square test. A 2-tailed p-value less than 0.05 were considered as statistically significant. Univariate and multivariate logistic regression analysis were performed to confirm the association. Results: The study revealed that not playing outdoor games (OR=3.09; 95% CI 1.46, 6.54), playing video/ TV/mobile games (OR=4.14; 95% CI 1.97-8.67), no sun exposure (OR=2.42; 95% CI 1.25-4.67), no milk consumption (OR=3.01; 95% CI 1.38-6.57), no sea fish consumption (OR=2.20; 95% CI 1.19-4.08) and not exclusively breastfeeding (OR=2.03; 95% CI 1.14-3.63) were significantly associated with vitamin D deficiency. Conclusion: We concluded that improper lifestyles and nutritional habits are the key determinants of Vitamin D deficiency among Bangladeshi children. Strategy for hypovitaminosis D prevention should be implemented immediately, which includes vitamin D supplementation of breastfed infants and ensuring adequate maternal vitamin D status during pregnancy. Also an awareness program should be initiated to promote a healthy lifestyle and to improve nutritional habits.